Experiencias disociativas y sueños: Explorando relaciones con el tipo de disociación (Revista Puertorriqueña de Psicologia, 2016)
Studies with the Dissociative Experiences Scale (DES) have identified items of the scale that ate more related to psychopathological conditions than other items (DES-T Items). The research reported here assesses the importance of these DES items and the absorption items of the scale as predictors of dream recall, lucid dreams and vivid dreams. A questionnaire containing the revised form of the DES and a variety of questions about dreams and other expriences was administered to students of an American community college (N=308). analyses showed that the absorption (non-pathological) item of the scale were better predictors of the dream variables than the items related to pathology in previous research. Results such as this show the importance of considering type of dissociation in our research on the subject.